2018
DOI: 10.1002/mc.22853
|View full text |Cite
|
Sign up to set email alerts
|

KAP1 inhibits the Raf‐MEK‐ERK pathway to promote tumorigenesis in A549 lung cancer cells

Abstract: Aberrant activation of the Raf-MEK-ERK pathway has frequently been associated with various cancers, especially lung cancer. However, the key regulators of this pathway are largely unknown. Using functional proteomics screening, we found that KAP1 interacts with c-Raf. Knocking out KAP1 decreased c-Raf phosphorylation at serine 259 and increased its phosphorylation at serine 338, which activated MEK and ERK. We detected higher KAP1 expression in lung cancer tissues than in normal peri-tumoral tissues. KAP1 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…It has been reported that Akt was employed in processes during cell cycle by downregulating p21Cip1 23 . In addition studies also implied that MAPK signaling pathways, especially Erk and JNK, were also engaged in cell proliferation along with apoptosis 24 - 26 . To analyze the potential molecular mechanism of influences of quisinostat on MAPK signaling pathways, Western blotting was employed to assess expressions of AKT kinase and JNK kinase in HCCLM3 and SMMC-7721 cells.…”
Section: Resultsmentioning
confidence: 98%
“…It has been reported that Akt was employed in processes during cell cycle by downregulating p21Cip1 23 . In addition studies also implied that MAPK signaling pathways, especially Erk and JNK, were also engaged in cell proliferation along with apoptosis 24 - 26 . To analyze the potential molecular mechanism of influences of quisinostat on MAPK signaling pathways, Western blotting was employed to assess expressions of AKT kinase and JNK kinase in HCCLM3 and SMMC-7721 cells.…”
Section: Resultsmentioning
confidence: 98%
“…Given its importance in regulating a broad range of physiologic processes, it is not surprising that KAP1 has been co-opted in pathologic conditions. Indeed, KAP1 haplo-insufficiency facilitates obesity (Dalgaard et al, 2016), is amplified in cancer (Hector et al, 2012;Ho et al, 2009;Liu et al, 2013a;Wang et al, 2013Wang et al, , 2016, is a potential biomarker for colorectal cancer (CRC) (Gawel et al, 2019;Shiromizu et al, 2017), is required for xenograft proliferation in nude mice (Chen et al, 2014;Wu et al, 2018), and increases transforming growth factor b (TGF-b)-induced epithelial-to-mesenchymal transition (Xu et al, 2009), and its expression negatively correlates with cancer patient survival (Cui et al, 2014;Liu et al, 2013a). Despite this compelling in vivo relevance, the molecular mechanisms underlying KAP1 transcriptional regulation in physiologic and pathologic states remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that the Raf/MEK/ERK signaling pathway is closely associated with tumorigenesis in multiple types of malignant tumor, including colon and lung cancer (29)(30)(31). A previous study has revealed that diallyl disulfide treatment elevates the apoptotic rate by downregulating the RAF/MEK/ERK signaling pathway in esophageal carcinoma cells (32).…”
Section: Discussionmentioning
confidence: 99%